KNOWLEDGE — THE GUIDING STAR OF HUMAN LIFE - Nosirjonova Mumtozbegim Nodirbek qizi; Mannobov Abdumalik Mansurjon oʻgʻli (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation. This article, written from the perspective of a 6th grade student from Uzbekistan, explores the transformative power of knowledge in human life. It examines how knowledge illuminates the path forward when people face trials and opportunities, how it develops critical thinking, fosters independence, and drives both personal and societal progress. Through reasoned reflection and motivating examples, the article encourages every young reader to pursue learning with patience, diligence, and determination — for knowledge is a treasure that neither ages nor fades.